HOTS-oriented mathematical problem-solving ability reviewed from the students’ learning styles - Rejeki, Sri; Sheilawati, Kharisa Rinandyta; Setyaningsih, Rini (Universitas Ahmad Dahlan, 2024)
This research aims to analyze the students' mathematical problem-solving abilities in solving higher order thinking skills (HOTS) oriented mathematics problems in algebra material, particularly reviewed from their learning styles. This research used a qualitative descriptive method. The subjects of this research consisted of 6 students of Class VIII Science 4 at MTs Negeri 1 Surakarta. Data collection techniques consist of questionnaires, tests, and interviews. Data analysis techniques consist of data presentation, data reduction, and conclusion. The results of this research are the mathematical problem-solving abilities of Class VIII Science 4 students based on the visual learning style type which is the same as the auditory learning style in solving problems on linear equation system in two variable material, namely being able to carry out up to the fourth stage of Polya (understanding problems, planning, solving problems, and looking back at the process). Meanwhile, the mathematical problem-solving abilities of Class VIII Science 4 students are based on the kinesthetic learning style, namely implementing up to the third stage of Polya (understanding the problem, planning, and solving the problem).